Good or Bad Governance for Whom? Governance is a Trojan Horse for Capital Expansion in Pati, Indonesia - Novianto, Arif (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2024)
Governance as theory and practice, since the end of the 20th century, has been disseminated as the best form of public management. This notion of governance emphasizes reducing state actor authority, and in the name of participation, the voice of the state actor is positioned on par with the voices of private actors and civil society. To support the concept of governance, international organizations and financial institutions (United Nation, World Bank & IMF) promote the principles of "good governance" as the antithesis of "bad governance" which is characterized as corrupt, undemocratic and detrimental to the people. This research challenges governance theory and practice, with a case study of Indocement Ltd (Heidelberg Cement Group) expansion in Central Java, Indonesia. This research uses an ethnographic method, which was carried out in two periods, in 2014-2015 and 2017-2018. The contribution of this research is that instead of being happily accepted by the people, governance and the principles of good governance were actually opposed by the grassroots community in the case of Indocement Ltd's development plan in the Kendeng Mountains, Pati Regency, Central Java. This resistance was motivated by the use of governance and the principles of "good governance" to force the construction of a cement factory. In fighting against these problems, the people's movement advocated democracy from below through a counter-hegemonic movement that involved people, until finally it succeeded in thwarting a project to build a cement factory in their place. For people who reject the cement factory plan, governance is "good" for capital, but "bad" for the environment and people's livelihoods.